Cos x = -12/13
sin x = -sqrt(13^2 - 12^2) / 13 = -5/13
tan x = 5/12
tan x/2 = (1 - cos x) / sin x = 1 - (-12/13) / -5/13 = 25/13 * -13/5 = -5
2sin^2 x/2 = 1 - cos x = 1 - (-12/13) = 25/13
sin^2 x/2 = 25/13 / 2 = 25/26
sin x/2 = 5/√26
sin x/2 / cos x/2 = tan x/2
cos x/2 = sin x/2 / tan x/2 = 5/√26 / -5 = -1/√26
sin x/2 = 5/√26
cos x/2 = -1/√26
tan x/2 = -5
Answer:
it is
possible
Step-by-step explanation:
<u>sum of the two shortest sides must be greater than the third side.</u>
so
4+7 < 9
11<9
condition satisfies ,
hence proved , we can draw
Answer:
-4w+1
Step-by-step explanation:
Simplify the expression.
Answer:
<em>(C). {3} </em>
Step-by-step explanation:
=
+
( x ≠ - 1 )
-
+
= 0
-
= 0
= 0 ⇒ <em>x = 3</em>
Answer:
AB = 142
Step-by-step explanation:
If M is the midpoint, then AM = MB
6x+5 = 7x -6
Subtract 6x from each side
6x-6x+5 = 7x-6x -6
5 = x-6
Add 6 to each side
5+6 = x-6+6
11=x
We want to find AB
AB = 6x+5+7x-6
AB = 13x -1
= 13(11) -1
=143-1
= 142